Bearfence: an innovative prevention system for bear management and re-education - Ossi, F.; Molteni, D.; Picco, G. P.; Murphy, A.; Sforna, T.; Avenia, S.; Svaizer, N.; Pedrotti, L.; Groff, C.; Salmistraro, S.; Scaravelli, D.; Cagnacci, F. (country:SI, 2018)
The population of reintroduced brown bear (Ursus Arctos) in Central Alps (Trentino, Italy) successfully expanded to 50–60 individuals from its inception in 2000. Within the population, some confident brown bears approached and used anthropic resources, raising conflicts. A close understanding of behaviors of use of anthropic resources and development of related management measures are crucial to increase acceptance by local stakeholders and ultimately to preserve the conservation of the reintroduced population. In this context, we developed BEARFENCE, an innovative technological system that has the double scope to prevent bear damages and to re-educate confident individuals. BEARFENCE consists of a tag apposed on the bear and of several fixed devices which are deployed near sensitive resources, such as beehives or livestock night recovers. The fixed elements detect the presence of the tagged individual, to then activate a randomized sequence of deterrents, which are designed to minimize the risk that the bear habituates to the prevention system. Moreover, in case of bear detection an alert message is sent to the emergency personnel. We performed a long-term test of BEARFENCE under different deterring scenarios, to evaluate its performance. To do this, we repeatedly simulated the detection of a bear, and we evaluated the correctness of the dissuasion protocol by comparing the expected and observed BEARFENCE response. We found that both simulated bear detections and the consequent deterrents sequences worked properly in all instances (n = 112). We foresee BEARFENCE application to be effective in the Alpine brown bear coexistence context, as well also for other populations, and other bear species. We conclude that the technical advances promoted by BEARFENCE represent an example of how combining technology with wildlife management can represent a valuable way to ensuring a long-term coexistence of bears and humans.